Studi Komparasi Perilaku Keagamaan, Karakter Kepemimpinan, Antusias Belajar antara Mahasiswa dengan Latar Belakang Madrasah Aliyah dan Sekolah Menengah Atas - Khoirul Jazilah (Journal on Education, 2022)
The content of the research is to analyze differences in religious behavior, leadership character, enthusiasm for learning between students from Madrasah Aliyah and Senior High School backgrounds. The type of research is quantitative-comparative. The data collection technique uses a questionnaire. The data analysis technique uses Independent Sample T Test Statistics. The research population was second, fourth and sixth semester students with 101 students as respondents. The variables in this research are religious behavior, leadership character, enthusiasm for learning. Research result: (1) there is no significant difference in religious behavior between students from Madrasah Aliyah and High School backgrounds at the Uluwiyah Mojokerto Islamic Institute. This can be seen from the calculated t value < t table (-0.515 < 1.984) with sig 0.608 > α = 0.05, df = 99, F = 1.206 with 0.275, mean difference -0.965, and standard error difference = 1.874. (2) there is no significant difference in leadership character between students from Madrasah Aliyah and High School backgrounds at the Uluwiyah Islamic Institute, Mojokerto. This can be seen from the value of t calculated < t table (-0.923 < 1.984) with sig 0.358 > α = 0.05, df = 99, F = 1.859 with 0.176, mean difference -1.576, and standard error difference = 1.707. 3) there is no significant difference in enthusiasm for learning between students from Madrasah Aliyah and High School backgrounds at the Uluwiyah Mojokerto Islamic Institute. This can be seen from the calculated value of t < t table (-1.341 < 1.984) with sig 0.183 > α = 0.05, df = 99, F = 0.038 with 0.845, mean difference -2.634, and standard error difference = 1.965